MODERN METHODS OF INTERNET PROMOTION IN THE DOOR MARKET - KOVALCHUK, Svitlana; FEDORKEVYCH, Yurii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
This article highlights current strategies and effective methods of promoting products in the door market via the Internet in the competitive struggle for sales markets. Analyzing a highly competitive industry, the authors examine various aspects of an effective online presence to increase store traffic and sales. The article focuses on the analysis and comparison of various modern methods of Internet promotion in the context of the door market, with an emphasis on determining the most effective approaches to their application, in particular, such as: social networks, search engine optimization, e-commerce, video marketing, cooperation with influencers, retargeting, content -marketing and adaptive web design. The authors examine each of these methods in detail, evaluating their cost, complexity of setup, and potential effectiveness for different target audiences. Special attention is paid to analyzing the needs of different market segments, such as: young professionals, married couples, older generations, eco-conscious buyers, developers, owners of commercial premises and real estate investors. The article examines exactly how strategies can help increase competitiveness and effectively attract the attention of the target audience. The authors emphasize the importance of a comprehensive approach and individual targeting of each segment, taking into account their unique needs and preferences. The article also includes recommendations for the optimal combination of various Internet marketing methods to maximize the effectiveness of marketing efforts in the door market. Conclusions and proposals are based on a deep analysis of modern trends in digital marketing, as well as on the experience of the author team in this field. The article contains practical recommendations for companies specializing in the sale of doors, which seek to successfully market their products via the Internet. In particular, modern trends and innovative approaches for optimizing electronic business in the field of door production and their implementation are considered. This work can be useful for marketers, door manufacturers, and anyone interested in developing effective Internet marketing strategies in specific markets.
Keywords: Internet promotion; door market; digital marketing; search engine optimization (SEO); contextual media advertising; targeted advertising; content marketing; retargeting; market segmentation; target audiences; marketing strategies; Internet marketing effectiveness